Pengaruh Bauran Pemasaran terhadap Peningkatan Omzet di Apotek Kimia Farma Kelud Kota Semarang - Tri Wahyuningsih; Ferika Indrasari; Cinthya Nisha Ristita; Defilia Anogra Riani (Journal of Pharmacy and Clinical Practice, 2025)
Increasingly fierce competition in the pharmaceutical retail industry requires pharmacies to implement effective marketing strategies to increase sales turnover. The 7P marketing mix, which includes product, price, place, promotion, personnel, process, and physical evidence, is a relevant strategic approach in the context of pharmaceutical marketing, although its implementation is limited by pharmaceutical regulations, particularly in terms of drug promotion. The purpose of this study was to determine the effect of the marketing mix on sales revenue growth at Kimia Farma Kelud Pharmacy in Semarang City. This study used a mixed-method approach with an observational design and was conducted from January to April 2024. Quantitative data were obtained from the monthly sales turnover reports of Kimia Farma Kelud Pharmacy sourced from the Point of Sales (POS) system during the period 2019–2023, while qualitative data were obtained through structured interviews with the Managing Pharmacist of the Pharmacy to describe the implementation of the 7P marketing mix. The sampling technique used total sampling. Data analysis was performed through normality tests, regression tests, and t-tests to determine the effect of the marketing mix on sales revenue growth. The results showed that the application of the 7P marketing mix had a positive and significant effect on sales revenue growth at Kimia Farma Kelud Pharmacy in Semarang City. This is evidenced by the positive regression coefficient value (β = 0.483) and significance value p = 0.003 (< 0.05), thus accepting the alternative hypothesis. Descriptive analysis shows a consistent upward trend in turnover from the pre-pandemic period, during the COVID-19 pandemic, to the new normal era. These findings indicate that the integrated and regulatory-compliant application of the 7P marketing mix is effective in improving sales performance and strengthening the competitiveness of pharmacies amid the dynamics of a competitive pharmaceutical market. Keywords: 7P marketing mix, sales turnover, pharmacies, pharmaceutical marketing strategy, pharmaceutical retail competitiveness.